Über die Tiefenwasserausbreitung im Weddellmeer und in der Scotia-See : numerische Untersuchungen der Transport- und Austauschprozesse in der Weddell-Scotia-Konfluenz-Zone - Schodlok, Michael P (Univ. Bremen, 2002)
WSDW, water mass spreading, numerical model, lagrangian trajectories, Weddell Scotia Confluence. - The deep Scotia Sea is filled with ventilated Weddell Sea Deep Water (WSDW). This in turn is an essential contributor to the ventilation of the World Ocean abyss. A primitive equation, hydrostatic, ocean general circulation model (BRIOS1.1) with terrain-following coordinate is used to investigate the water mass export from the Weddell Sea. The model is circumpolar focusing on the Weddell Sea, with particularly high resolution (2̃0 km) in the DOVETAIL area. The northern limb of the Weddell Gyre exhibits an eastward Weddell Sea Deep Water transport across 44ʿW of 24 Sv. Export rates of Weddell Sea Deep Water through gaps in theSouth Scotia Ridge are estimated to be 6.4 Sv with a semi-annual cycle of ± 0.6 Sv, which can be correlated to atmospheric cyclone activity and Weddell Gyre strength. Sensitivity studies considering extreme sea ice conditions in the Weddell Sea show higher (lower) exports in years of minimum (maximum) winter sea ice extent. This can be attributed to the local change of the surface stress achieved by wind and ice. Lagrangian ... : thesis